Percutaneous transhepatic cholangial drainage or antibiotic therapy worsens response to immunotherapy in advanced cholangiocarcinoma - Qingyu Huang; Fuhao Wang; Xiang Zhang; Jing Liu; Xue Dou; Rui Feng; Kunli Zhu; Shumei Jiang; Yun Zhang; Jinbo Yue (BMC Cancer, 2023)
Abstract Background Bile duct obstruction is a common issue for patients with advanced cholangiocarcinoma (CCA). Percutaneous transhepatic cholangial drainage (PTCD) is often required to relieve the obstruction. However, PTCD may alter the intestinal microbiota, which can affect the efficacy of immunotherapy. Antibiotics (ATB) can also have significant immunomodulatory effects by perturbing the gut microbiota. Therefore, this study aimed to investigate whether PTCD or ATB therapy is associated with overall survival (OS) or progression-free survival (PFS) in patients with advanced CCA receiving first-line chemotherapy plus immune checkpoint blockade (ICB) in clinical practice. We also explored whether the gut microbiota changes after receiving PTCD. Methods We conducted a single-center retrospective analysis of PTCD and ATB therapy in patients with advanced CCA. PTCD was performed before ICB initiation, and ATB was administered within 1 month before and 6 weeks after ICB initiation. Our primary outcomes were PFS and OS. Moreover, we used 16s rRNA sequencing to analyze fecal and bile samples obtained from patients who underwent PTCD. Results In total, 107 patients with CCA were included. Among patients who did not undergo PTCD, ICB plus chemotherapy significantly improved OS vs. chemotherapy alone (hazard ratio [HR] 0.21, 95% confidence interval [CI] 0.09–0.45, p < 0.0001). PFS was also significantly improved in patients who received ICB plus chemotherapy compared with chemotherapy alone (HR 0.36, 95% CI 0.16–0.80, p = 0.0024). However, ICB plus chemotherapy did not improve survival compared with chemotherapy alone among patients who received PTCD. Overall changes in the fecal microbiota of patients after PTCD involved significant reductions in which Escherichia − Shigella. Conclusions The use of ATB or PTCD in patients with CCA receiving ICB was associated with worse OS compared with chemotherapy alone, and PTCD affects the gut microbiota. Escherichia − Shigella was significantly reduced in feces of patients after PTCD.